KOMPARASI HASIL BELAJAR MATEMATIKA ANTARA MEDIA KONKRET DAN MEDIA GAMBAR DI SEKOLAH DASAR - Iskandar, Irfan; Margiati, Margiati; Asmayani, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to analyze the data on student learning outcomes in mathematics learning taught by using Media Images and Concrete Media in class IV of the 10th Element’ry School of East Pontianak. The method used is the experimental method. In this study, using Quasi Experimental Design with the form of Nonequivalent Control Group Design. The population in this study were all fourth grade students of State Elementary School 10 of East Pontianak, while the sample was obtained through drawing in all class IV. Based on the results of the draw, the research samples were obtained, namely class IV A (experimental class) and IV B (control class) which amounted to 70 students. The data collection technique used is a measurement technique and a data collection tool is an essay written test. Based on data analysis, the results of the experimental class post- test average of 75.21 and the control class post-test average of 69.23. Hypothesis test results using t-test (Polled Variance) obtained tcount = 1.81 while for dk (35 + 35 - 2 = 68) with a significant level α = 5% obtained t table = 1.672, which means thitung> t table, then Ha is accepted , this proves that there is a significant difference between student learning outcomes in mathematics learning by applying the use of concrete media and picture media in class IV of the 10th Elementary School of East Pontianak. Keywords: Comparation, Media Images, Concrete Media, Mathematics Learning, Learning Outcomes.